Substrate metabolism during exercise: sexual dimorphism and women`s specificities - Boisseau, N.; Isacco, L. (European Journal of Sport Science, 2022)
The aim of this review is to discuss sexual dimorphism of energy metabolism, and to describe the impact of women`s hormonal status on substrate oxidation during exercise. Many evidences indicate that sex steroids play a pivotal role in the sex-related differences of body composition and energy substrate storage. Compared with men, women rely more on fat and less on carbohydrates at the same relative exercise intensity. Scientific data suggest that 17-ß oestradiol is a key hormone for the regulation of body composition and substrate metabolism. However, in women, measurements with stable isotopic tracers did not highlight any difference in whole-body substrate oxidation rates between the follicular and luteal phases of the menstrual cycle during endurance exercise. The remaining discrepancies about the effect of menstrual cycle-related hormone fluctuations on substrate oxidation could be partly explained by the exercise intensity, which is an important regulator of substrate oxidation. Due to their specific nature and concentration, the synthetic ovarian hormones contained in oral contraceptives also influence substrate metabolism during endurance exercise. However, more studies are needed to confirm that oral contraceptives increase lipolytic activity during endurance exercise without any substantial (or detectable) effect on substrate utilization. Pregnancy and menopause also modify body composition and substrate utilization during exercise through specific hormonal fluctuations.